2022
DOI: 10.1186/s40560-022-00603-w
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy evaluation of mainstream and sidestream end-tidal carbon dioxide monitoring during noninvasive ventilation: a randomized crossover trial (MASCAT-NIV trial)

Abstract: Background The end-tidal partial pressure of carbon dioxide (PETCO2) can be used to estimate the arterial partial pressure of carbon dioxide (PaCO2) in patients who undergo mechanical ventilation via endotracheal intubation. However, no reliable method for measuring PETCO2 during noninvasive ventilation (NIV) has been established. The purpose of this study was to evaluate the correlation and agreement between PaCO2 and PETCO2 measured by these two methods and to compare them in patients who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The authors concluded that the results of previous studies monitoring ETCO 2 during NIV were mixed likely due to physiological issues and shortcomings of exhalation sample collection. (12)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the results of previous studies monitoring ETCO 2 during NIV were mixed likely due to physiological issues and shortcomings of exhalation sample collection. (12)…”
Section: Discussionmentioning
confidence: 99%
“…(8) There is some debate surrounding the correlation of ETCO2 to PaCO2, but several studies have found good correlation in healthy patients and patients with compromised pulmonary function who are spontaneously breathing. (9)(10)(11)(12) Capnography has been shown to be a valuable screening tool for mortality predictions in patients with sepsis. (13,14) Also, in penetrating trauma patients, capnography measurements correlate with serum lactate levels (an indicator of tissue hypoxia and shock) and can predict the odds of the patient requiring operative intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This is in obvious contrast to mainstream capnography, where the gas mixture is analyzed directly in the circuit. Previous studies in subjects during supine craniotomy and cardiac surgery in the operating room, during noninvasive ventilation in the ICU, and in spontaneously breathing subjects in the emergency room have shown more variable and less accurate etCO 2 measurements with sidestream capnography [ 17 , 18 , 22 , 23 ]. Similar findings come from studies in pediatric populations, especially during periods with higher respiratory rates [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is used for many applications like cardiopulmonary resuscitation, airway assessment, sedation, and analgesia [47]. It can be useful for the early recognition of potential breathing complications and the recognition of respiratory compromise or failure [44,48], allowing for prompt diagnosis and, consequently, a timely intervention or correction.…”
Section: End-tidal Monitoringmentioning
confidence: 99%